Истражување на перспективите за развој на електронска продажба на облека од македонските конфекциски производители - Томовска, Елена (Економски факултет, УКИМ, Скопје, 2011)
Although e-retail on a global level is approaching its maturity, it is still in embryonic stage on the developing Macedonian market. The purpose of this research is to investigate the current state of apparel e-retail and determine the perspectives for its development in Macedonia. The problem was approached from two aspects – consumers and apparel producers. Regarding the consumers the aim was to identify appropriate and distinct segments of potential internet consumers. To address the question a paper based survey was conducted, on a target population of frequent internet users. Factor analysis and cluster analysis were used to obtain a three-cluster solution, tested by a discriminant analysis (98.5 percent score). The created classification provides apparel retailers with a framework for targeting consumers in order to provide a closer fit between their offer and consumer needs. A mixed quantitative and qualitative survey was conducted among top management in apparel companies to investigate the attitudes of apparel producers towards e-retail and to define a framework for developing e-retail. The survey combined a paper-based questionnaire for drawing a general picture of their attitudes towards e-retail and in-depth interviews to provide deeper understanding of the subject. As a result an inter-operational framework for e-retail of Macedonian apparel was created.
An investigation into the development Perspectives for apparel e-retail in Macedonia
Докторска дисертација одбранета во 2011 година на Економскиот факултет во Скопје, под менторство на проф. д–р Сашо Јосимовски.
Keywords: apparel e-retail, consumer segmentation, e-retail strategy, Macedonian apparel production